The Number of the Modes in the Church Chantaccording to St. Maximus the Confessor - Ignatov, Lyubomir (Forum Theologicum Sardicense, 2025)
The Number of the Modes according to St. Maximus the Confessor. The author provides a symbolic and numerological interpretation of the number of musical modes in the 5th and 6th centuries, with a particular focus on the works of St. Maximus the Confessor.